정신병원 임상 실습 간호대학생의 정신병원 입원환자 대상 사이코드라마 참여 경험에 관한 질적 연구 - 전욱; Uk Jeon (한국사이코드라마학회지, 2025)
본 연구는 정신병원 입원환자를 대상으로 하는 사이코드라마에 참여한 정신병원 임상 실습 간호대학생의 경험을 심층적으로 탐구한 질적 연구이다. 연구 참여자는 2024년 10월부터 11월까지 정신병원에서 임상 실습을 수행하며 환자 대상 사이코드라마 활동에 참여한 간호대학생 12명이며, 자료 분석에는 Colaizzi의 현상학적 연구방법을 적용하였다. 심층 면담을 통해 수집된 자료를 분석한 결과, ‘편견에서 공감으로 이해의 확장’, ‘자기 성찰을 통한 변화와 성장’, ‘의심에서 전문적 관심으로의 전환’, ‘자신감 획득과 진로 탐색의 확장’ 등 4개 범주가 도출되었다. 연구 참여자들은 사이코드라마 참여를 통해 정신질환자에 대한 편견을 극복하고 자기 성찰을 통한 정서적·인격적 성장을 경험하였으며, 사이코드라마의 치료적 효과를 인식하고 이에 관한 관심이 깊어졌다. 이런 경험들은 임상 실습에 대한 자신감과 정신간호 분야 진로 관심을 높이는 데 기여하였다. 본 연구는 사이코드라마가 정신질환자와의 관계 형성은 물론, 간호대학생의 전문직 정체성 함양에 효과적인 교육 도구가 될 수 있음을 보여주었으며, 향후 임상 실습 교육 현장에서 사이코드라마의 적극적인 활용을 제언한다. This study is a qualitative study to explore in-depth the experiences of nursing students in mental hospitals who participated in psychodrama for inpatients in mental hospitals. The study participants were 12 nursing students who conducted clinical practice at mental hospitals from October to November 2024 and participated in psychodrama activities for patients, and Colaizzi's phenomenological research method was applied to data analysis. Participants in the study overcame prejudice and fear against psychotic patients through psychodrama participation, expanded empathy and understanding, and experienced emotional and personal growth through self-reflection. In addition, interest in psychodrama increased as they recognized its therapeutic effect. These experiences have contributed to enhancing confidence in clinical practice and expanding career interest in the field of mental nursing. This study showed that psychodrama can be an effective educational tool not only for forming relationships with psychotic patients but also for establishing an identity as a professional nurse for nursing students, and accordingly, it is suggested that the active use of psychodrama in the clinical practice field of nursing education is necessary in the future.